Authentic leadership in the educational system and in nursing education: an integrative review - Cezar Augusto da Silva Flores; Suellen Rodrigues de Oliveira Maier; André Almeida de Moura; Alexandre Pazetto Balsanelli; Bruna Moreno Dias; Andrea Bernardes (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to identify and analyze the knowledge produced in literature about authentic leadership in the educational system, as well as in nursing education. Methods: an integrative review, carried out in the Scopus, Web of Science, CINAHL, MEDLINE/PubMed, ERIC, LILACS databases. Articles that addressed authentic leadership in the educational system from a general perspective and within the nursing scope, as well as teaching practices of this leadership model, were eligible. Results: twenty-three articles met the inclusion criteria, most published in 2019, highlighting studies in the context of teaching, with a predominance in the nursing course and which were synthesized into three thematic categories. Final Considerations: it was found that the higher the levels of authentic leadership in the educational system, the higher the rates of other positive factors related to it, such as trust, involvement, academic optimism, responsibility, creativity, among others.